The FtsH protease slr0228 is important for quality control of photosystem II in the thylakoid membrane of Synechocystis sp. PCC 6803 - Komenda, Josef; Barker, Myles; Kuviková, Stanislava; Vries, Remco de; Mullineaux, Conrad W; Tichý, Martin; Nixon, Peter J (The Journal of biological chemistry, 2006)
The cyanobacterium Synechocystis sp. PCC 6803 contains four members of the FtsH protease family. One of these, FtsH (slr0228), has been implicated recently in the repair of photodamaged photosystem II (PSII) complexes. We have demonstrated here, using a combination of blue native PAGE, radiolabeling, and immunoblotting, that FtsH (slr0228) is required for selective replacement of the D1 reaction center subunit in both wild type PSII complexes and in PSII subcomplexes lacking the PSII chlorophyll a-binding subunit CP43. To test whether FtsH (slr0228) has a more general role in protein quality control in vivo, we have studied the synthesis and degradation of PSII subunits in wild type and in defined insertion and missense mutants incapable of proper assembly of the PSII holoenzyme. We discovered that, when the gene encoding FtsH (slr0228) was disrupted in these strains, the overall level of assembly intermediates and unassembled PSII proteins markedly increased. Pulse-chase experiments showed that this was due to reduced rates of degradation in vivo. Importantly, analysis of epitope-tagged and green fluorescent protein-tagged strains revealed that slr0228 was present in the thylakoid and not the cytoplasmic membrane. Overall, our results show that FtsH (slr0228) plays an important role in controlling the removal of PSII subunits from the thylakoid membrane and is not restricted to selective D1 turnover.
Keywords: buněčná membrána; Electrophoresis, Polyacrylamide Gel; Biochemical Phenomena; Photosystem II Protein Complex; imunoblotting; chloroplasty; 2D gelová elektroforéza; Epitopes; elektroforéza v polyakrylamidovém gelu; zelené fluorescenční proteiny; světlo; tylakoidy; Metalloendopeptidases; Microscopy, Confocal; Mutation, Missense; Peptide Hydrolases; Protein Binding; metaloendopeptidasy; Thylakoids; mutace; Green Fluorescent Proteins; financování organizované; konfokální mikroskopie; Time Factors; Financing, Organized; Genotype; plazmidy; časové faktory; Light; fotosystém II (proteinový komplex); missense mutace; Biochemistry; vazba proteinů; biochemické jevy; Electrophoresis, Gel, Two-Dimensional; Chloroplasts; Immunoblotting; Synechocystis; genotyp; biochemie; Cell Membrane; Mutation; Plasmids; epitopy; proteasy